Coronary artery disease in patients with rheumatic valvular heart disease- An analysis from eastern India - Avik Karak; Novonil Deb; Dibbendu Khanra; Santanu Guha; Anindya Mukherjee (Indian Heart Journal, 2024)
Introduction: There is insufficient information on the angiographic characteristics of individuals with rheumatic valvular heart disease (VHD) from eastern India. The objective of this research is to gather important data in this area to aid the best surgical outcomes for patients with rheumatic VHD. Materials and methods: 978 consecutive patients with rheumatic VHD, scheduled for surgical intervention, were recruited. Result and conclusion: Mitral valve involvement was observed in 66.1 %, aortic valve in 7.3 % and both valves in 26.6 %. Patients with CAD had significantly higher proportions of severe aortic stenosis (AS). Therefore, addressing the risk factors for CAD is crucial in patients with rheumatic VHD.